The Effect of Income on the Benefit of Consumption of Pusong Fishermen in Lhokseumawe City - Aidilla Fitri; Damanhur Abbasb (Research Collaboration Community (RCC), 2020)
This study aims to determine and analyze the effect of income on the consumption benefit of Pusong fishermen in Lhokseumawe City. The results of the research show that partially the income has a significant influence on the consumption benefit of Pusong fishermen in Lhokseumawe City. An adjusted R square figure of 0.775 indicates that 75.5% of the benefit variable consumption bias explains the income used in the regression equation. While the remaining 24.5% is influenced by other variables not included in this study.